(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
This article describes the design process and implementation of a low cost system that allows quantitatively measure some path variables involved in the execution of the movements of weightlifting in boot mode described. Initially the theoretical aspect of biomechanical analysis mode is scanned and, moreover, the different techniques for the detection and tracking of objects in the scene are analyzed. Motion capture is performed through a standard video camera and image processing is done with the OpenCV library on the Raspberry Pi platform; data is displayed in a wxWidgets-based GUI that allows you to observe the movement made video besides the kinematic trajectory and velocity and acceleration information. In the process of design and planning method Work Breakdown Structure is used (WBS by name in English Work Breakdown Structure) which identifies elements of software, hardware, services and other components necessary for the realization of the prototype. Once implemented the prototype performance tests are performed on stage to validate the design. This system attempts to meet the needs of the coach to objectively evaluate the important positions that are difficult to discern with the naked eye due to the high speed of execution as well as the subjectivity of the observer or visual memory. With this information it is possible to identify the athlete to strengthen weaknesses and improve performance.